Peran Pemaafan terhadap Kepuasan Pernikahan: A Literature Review - Ardhito Faza Akhnaf; Aqsa Vaca; Resdiyanti Permata Putri; Nanum Sofia (Psychopolytan : Jurnal Psikologi, 2024)
Divorce cases in Indonesia continue to increase every year with a variety of conflicting problems. Declining marital satisfaction is the cause of the increasing divorce rate. It is important to have an effective strategy to be able to maintain satisfaction in marriage, one of which is forgiveness. Forgiveness is an alternative solution that can help couples solve and prevent problems in the marriage relationship. This study aims to provide an overview of the relationship between forgiveness and marital satisfaction. This study is a literature review with search articles from the Google Scholar, ProQuest, PubMed and EBSCOHost databases. The search results obtained 15 articles that match the inclusion criteria. The results of this study reveal that forgiveness increases marital satisfaction in various cultural contexts. Marital satisfaction is also influenced by other factors such as gender and marriage length.